Bilateral emphysematous pyelonephritis and emphysematous cystitis: a rare case report - Šabotić, Irfan; Habibović, Ahmo; Ćorović, Irfan; Habibović, Selma (Vojnosanitetski pregled, 2025)
Introduction. Emphysematous pyelonephritis (EPN) is a rare type of severe kidney infection characterized by gas formation in the renal parenchyma, collecting system, or surrounding perinephric tissues. Emphysematous cystitis (EC) is a rare, potentially fatal condition characterized by the presence of gas in the bladder wall and lumen. We present a rare case of EPN with EC in a patient with diabetes mellitus (DM). Case report. A 38-year-old female patient with poorly regulated DM was referred to the Department of Urology at the General Hospital in Novi Pazar, Serbia, with malaise, fever, and flank and suprapubic pain. After physical examination, laboratory analyses, and radiological diagnostics, the diagnosis of bilateral EPN with EC was established. Throughout the hospitalization, the patient remained hemodynamically stable with preserved diuresis. The patient’s urine and blood cultures were negative. The patient was treated with intravenous fluids and antibiotics (metronidazole, vancomycin, and meropenem). No other invasive form of treatment was needed due to successful conservative treatment. Conclusion. A timely diagnosis and rapid inclusion of specific antibiotic therapies enables the avoidance of the need for invasive forms of treatment in patients with EPN and EC. The conservative management of the presented patient was successful.